On the feasibility of simple brain-computer interface systems for enabling children with severe physical disabilities to explore independent movement - Floreani, Erica D.; Rowley, Danette; Kelly, Dion; Kinney-Lang, Eli; Kirton, Adam (Frontiers in Human Neuroscience, 2022)
Introduction: Children with severe physical disabilities are denied their fundamental right to move, restricting their development, independence, and participation in life. Brain-computer interfaces (BCIs) could enable children with complex physical needs to access power mobility (PM) devices, which could help them move safely and independently. BCIs have been studied for PM control for adults but remain unexamined in children. In this study, we explored the feasibility of BCI-enabled PM control for children with severe physical disabilities, assessing BCI performance, standard PM skills and tolerability of BCI. Methods: Patient-oriented pilot trial. Eight children with quadriplegic cerebral palsy attended two sessions where they used a simple, commercial-grade BCI system to activate a PM trainer device. Performance was assessed through controlled activation trials (holding the PM device still or activating it upon verbal and visual cueing), and basic PM skills (driving time, number of activations, stopping) were assessed through distance trials. Setup and calibration times, headset tolerability, workload, and patient/caregiver experience were also evaluated. Results: All participants completed the study with favourable tolerability and no serious adverse events or technological challenges. Average control accuracy was 78.3% ± 12.1%, participants were more reliably able to activate (95.7% ± 11.3%) than hold still (62.1% ± 23.7%). Possible positive trends were observed between performance and prior BCI experience and age. Participants were able to drive the PM device continuously an average of 1.5 meters for 3.0 seconds. They were able to stop at a target 53.1% ± 23.3% of the time, with significant variability. Participants tolerated the headset well, experienced mild-to-moderate workload and setup/calibration times were found to be practical. Participants were proud of their performance and both participants and families were eager to participate in future power mobility sessions. Discussion: BCI-enabled PM access appears feasible in disabled children based on evaluations of performance, tolerability, workload and setup/calibration. Performance was comparable to existing pediatric BCI literature and surpasses established cut-off thresholds (70%) of “effective” BCI use. Participants exhibited PM skills that would categorize them as “emerging operational learners”. Continued exploration of BCI-enabled PM for children with severe physical disabilities is justified.